Pragmatic abilities of children with severe to profound hearing loss - Vaidya, Hemangi; Waknis, Aarti P.; Deshpande, Shweta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Western studies indicate that children with hearing impairment (CHI) are at risk of pragmatic delay due to their delayed language development. Pragmatics is influenced by culture. Hence the objective of the study was to compare the pragmatic skills of Marathi speaking CHI using hearing devices and typically developing children (TDC) matched according to their expressive language age, chronological age, and hearing age. Methods: Group I included 40 CHI using a hearing device having a chronological age range of 24 to 68 months, with an expressive language age of 6 to 48 months on receptive-expressive emergent language scale (REELS) and with a hearing age in the range of 12 to 36 months. Group II consisted of 40 TDC in the age range of 6 to 48 months. Checklist for assessment of pragmatics of pre-schoolerswas administered for assessment of pragmatics to children in both the groups. Results: Statistical analysis using unpaired t test indicated that there was a significant difference in pragmatic skills of the two groups when they were matched on the basis of their chronological and expressive language age (p<0.01), but there was no significant difference between the two groups when they were matched on the basis of their hearing age (p>0.01). Conclusions: Pragmatic ability is delayed in CHI and is more a function of hearing age than chronological age or expressive language age. Thus, pragmatic abilities should be assessed and intervention provided if required for CHI even if they have good expressive ability.